Genotype × Environment Interactions for a Diverse Set of Sweetpotato Clones Evaluated across Varying Ecogeographic Conditions in Peru - Grüneberg, W.J.; Manrique, K.; Zhang, D.; Hermann, M. (Wiley, 2005)
Sweetpotato [Ipomoea batatas (L.) Lam.] is cultivated across a wide range of agrogeographical conditions. The objectives of this study were to analyze genotype × environment (G × E) interactions for sweetpotato yield (i.e., storage root yield, biomass, harvest index) and nutritional traits [i.e., root dry matter (RDM), starch (STA), and β-carotene (BCR) content; and leaf carotene (BCL) and chlorophyll (CHL) content] in multienvironmental trials (MET) across ecogeographic regions. Nine clones of diverse origins were tested and compared with check clones at seven locations in Peru using two N treatments (N = 0 or 80 kg ha−1). The G × E analysis was conducted with regression, additive main effects and multiplicative interaction (AMMI), and cluster analyses. The G × E interactions were smaller than the genetic variation of nutritional traits. The G × E interactions were larger or nearly equal to the genetic variation of yield traits (except harvest index), and were mainly determined by subsets of genotypes and environments. The contribution of N input to G × E was often not significant. Genotypes were observed with wide adaptation and high yields (about 19 to 22 Mg ha−1) across all three environmental groups that were derived from the cluster analysis. However, a specifically adapted genotype was observed with considerable yield advantage over all widely-adapted genotypes in low-yielding environments (from 9 to 18 Mg ha−1). Locations differed in their selection ability for storage root yield. We concluded that it is possible to breed for high yield and wide adaptability in sweetpotato in Peru, and it can be ensured that low-yielding or marginal environments are not neglected in breeding efforts.